2. PENERAPAN MODEL PEMBELAJARAAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DI SMK NEGERI 1 KABUPATEN PADANG LAWAS - Nenni Herawati Siregar; Yuni Rhamayanti; Nova Christina Dewi (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2022)
From the results of the validity of the first cycle student problem solving test instrument above, it was found that all items had a minimum validation correlation of moderate category, so that all items could be used for evaluation in this study. the results of the difficulty level of the problem-solving ability test instrument above, it was found that the percentage interval of the difficulty level of the questions was at 27%-73%, with the minimum item category being moderate. All questions are not too difficult and not too easy, so they can be used for evaluation in this study. The implementation stages of this classroom action research include: Action planning, In this stage a plan will be made in the form of activities that will be carried out by the teacher in planning classroom action research on the application of problem-based learning strategies, Implementation of actions, In this stage, the teacher conveys the competencies to be achieved during the learning process, Observation, In this stage, observations are made of student and teacher activities in the learning process, Reflection. At this stage, classroom action research will continue if the level of problem-solving ability of students in the circle material mathematics lesson is marked by student learning mastery that has not reached 80% in the good category